1998
DOI: 10.1111/j.2042-7158.1998.tb06901.x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Activities of Hepatic Antioxidant Defence Enzymes in Developing Chick Embryos After Glucocorticoid Administration - A Factor to Produce Some Adverse Effects?

Abstract: Liver tissue is one of the principal targets of glucocorticoids, therefore changes in the balance between hepatic oxidative and reductive capacity may greatly influence adverse effects of glucocorticoid therapy. In this study, effects of glucocorticoid on the activities of hepatic antioxidant defence enzymes were examined by using developing chick embryos. After the administration of 0.25 micromol hydrocortisone sodium succinate, a typical glucocorticoid, to 15-day-old chick embryos, glutathione peroxidase, gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…1996). The increase in plasma levels of glucocorticoids may be partially responsible for the inhibition of this enzyme in the tumor‐bearing rats (Argiles and Azcon‐Bieto 1988; Lee et al . 1998).…”
Section: Discussionmentioning
confidence: 99%
“…1996). The increase in plasma levels of glucocorticoids may be partially responsible for the inhibition of this enzyme in the tumor‐bearing rats (Argiles and Azcon‐Bieto 1988; Lee et al . 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Effect of thyroxine (T4) on the elevation in serum triglyceride and non-esteri®ed fatty acid (NEFA) In chick embryos, GC alters the activities of antioxidant defense enzymes in the liver (Lee, Iwatsuru and Nishigori, 1998), which can result in the elevation of LPO in humoral components such as liver. Based on our previous ®ndings, GC-induced cataracts may be induced by oxidative stress that possibly arises in the liver (Nishigori et al, 1984b;Lee et al, 1991;Setogawa et al, 1994;Watanabe et al, 2000).…”
Section: Table IIImentioning
confidence: 99%
“…Therefore, it was surprising to find a decrease in GSH content of the alveolar epithelial cells in this study. Only the ocular lens is known to show a decrease in GSH levels after GC treatment, which might lead to cataracts as observed in man and animal (Lee et al 1998;Setogawa et al 1994). On the other hand, Rahman et al (1999) also found a decrease of glutamylcysteine synthetase heavy chain (the catalytic subunit of the rate limiting enzyme in glutathione synthesis) in A549 cells, leading to a decreased GSH content, after dexamethasone administration.…”
Section: Discussionmentioning
confidence: 97%